2020
DOI: 10.1111/pce.13754
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of sun‐induced chlorophyll fluorescence and reflectance to detect stress‐induced variations in canopy photosynthesis

Abstract: Passive measurement of sun‐induced chlorophyll fluorescence (F) represents the most promising tool to quantify changes in photosynthetic functioning on a large scale. However, the complex relationship between this signal and other photosynthesis‐related processes restricts its interpretation under stress conditions. To address this issue, we conducted a field campaign by combining daily airborne and ground‐based measurements of F (normalized to photosynthetically active radiation), reflectance and surface temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…However, findings from the PAM fluorescence literature show that this is an oversimplification at small spatial and temporal scales, one that may undermine the utility of the SIF signal as part of a complex, but fundamental biophysical process. Previous studies using herbicides that fully inhibit P ET show increased SIF after treatment (Pinto et al, 2020; Rossini et al, 2015), indicating a clear linkage to leaf‐level energy partitioning, though with the opposite trend as satellite‐based SIF‐GPP relationships. In order to take full advantage of information provided by remotely measured chlorophyll fluorescence, a fuller picture of energy partitioning on the ground is needed.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, findings from the PAM fluorescence literature show that this is an oversimplification at small spatial and temporal scales, one that may undermine the utility of the SIF signal as part of a complex, but fundamental biophysical process. Previous studies using herbicides that fully inhibit P ET show increased SIF after treatment (Pinto et al, 2020; Rossini et al, 2015), indicating a clear linkage to leaf‐level energy partitioning, though with the opposite trend as satellite‐based SIF‐GPP relationships. In order to take full advantage of information provided by remotely measured chlorophyll fluorescence, a fuller picture of energy partitioning on the ground is needed.…”
Section: Discussionmentioning
confidence: 86%
“…Previous work on this question has involved intermediate‐scale measurements from towers or airborne platforms, and some authors report sufficient agreement across scales to allow for the creation of methods for downscaling satellite data using transformed tower‐based measurements (Duveiller & Cescatti, 2016). However, spatial or temporal aggregation is often employed: Though some authors have measured changes in SIF over a period of hours following herbicide application (Pinto et al, 2020), correlations in daily mean tower‐based SIF retrievals and flux tower‐based GPP are more commonly reported (H. Yang et al, 2017; Wohlfahrt et al, 2018). While this aggregation may be justified in the context of other studies reporting linear scaling from instantaneous to monthly SIF‐GPP relationships (albeit at large spatial scales) (Wood et al, 2017), averaging across large diel variations limits the ability to track rapid changes in physiological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Pinto et al (2016) was first to report a proof of concept that high-resolution imaging spectrometers can provide the spatial pattern of SIF in order to quantify photosynthetic functions at canopy level. More recently, Pinto et al (2020) have provided more convincing evidence at a larger spatial scale that the dynamics in PRI and SIF can potentially be linked to photochemical and nonphotochemical events in plants during stress-induced scenarios. The maturity of SIF and ρ measurements at higher spatial and temporal resolutions will enable the scientific community to generate a vast amount of data in order to provide more dynamic empirical correlations between the light-dependent signals and biological events.…”
Section: Towards Remote Sensing Of Photosynthesismentioning
confidence: 99%
“…This appeared to be inconsistent with previous studies that reported the decoupling of SIF emissions and the carbon reactions of photosynthesis under certain conditions. For example, SIF emissions showed a rapid increase shortly after the application of a herbicide, resulting in a large reduction in CO 2 assimilation rates [37]. Liu et al [38] showed that the GPP of C3 crops exhibited so-called 'midday depression', a stable or even decreasing trend in photosynthesis at high light, whereas an increase in the SIF curve was observed.…”
Section: Discussionmentioning
confidence: 99%